Hubungan Interaktif Edukatif Guru dan Peserta Didik - Uswatun Umi Zarhasih; Muhammad Yasin (AL-AMIYAH: Jurnal Ilmiah Multidisiplin, 2024)
Abstract The educative interactive relationship between teachers and learners is significant in the context of education it creates a positive learning environment and supports the development of learners. The formulation of the problem is how is the educational interaction between teachers and students at MTs. Hubbul Wathon Sangatta Selatan? What are the positive and negative impacts of the educational interaction of teachers and students? Researchers used a type of field research. For the approach, researchers used a descriptive mode qualitative method approach. Researchers conducted interviews and observations at the location for data collection techniques and for data analysis using data condensation, data presentation, depiction and conclusion. The results of the research are found in several activities, for example on exams or formative assessments where students are given exams or assignments to make work to measure students' understanding of the material that has been learned, the teaching and learning process, extracurricular activities and due to the tasks given by the teacher so that it can provoke students to interact. Then the positive impact. a) increased motivation to learn because they have a high sense of trust and safety when interacting. b) the class can help develop students' social skills. c) students have a good understanding when conveyed by the teacher to affect the value negative impact 1) Learners who have too close of a bond with the teacher.